Production and Turnover of Planktonic Bacteria in Two Southeastern Blackwater Rivers - Edwards, Richard T. (1986)
Production by attached and free-living planktonic bacteria in two blackwater rivers in the Southeastern United States was measured over a period of 14 months by using the rate of incorporation of [methyl-(3)H]thymidine into DNA. Production rates and biomass dynamics were compared to determine the potential for in situ production to supply planktonic biomass. Bacterial production in these rivers was moderate and varied seasonally. Rates varied from 0.058 to 2.120 mg of C m(−3) h(−1) in the Ogeechee River and from 0.002 to 2.418 mg of C m(−3) h(−1) in Black Creek. Regressions of growth rate on various environmental variables showed that temperature and total dissolved organic carbon concentration were the best predictors of growth. Although attached bacteria were <21% of the total biomass, they accounted for up to 53% of the total production. Turnover times for attached bacteria ranged from <1 day to >3 years depending on season. Turnover times of free-living bacteria varied from 4.4 days to 11.8 years. Comparisons of biomass with production indicated that during most seasons, the majority of bacterial biomass in these rivers was of allochthonous origin. During summer, when water temperatures were high, bacterial growth in the river may have supplied a greater percentage of the standing stock of bacteria than allochthonous inputs.